(untitled) (GYMNASIUM, 2020)
The aim of the research was to obtain useful information concerning strength preparation of the senior men’s handball players, completing and applying a questionnaire to achieve this purpose. Every question has a precise objective, in order to obtain useful data concerning physical preparation, especially strength, of the senior men’s handball players. The conclusions of this research, obtained after analyzing the answers from the questionnaire, require some adjustments in order to improve the physical preparation of the senior’s male handball players. In the handball game, the specialists specify the need to identify the specific manifestation forms of the strength as indispensable, and the knowledge of the relation of the strength with the other motor qualities is essential to determine its role and place in the general and specific physical training. For the practice of the handball game at a high level, the relationships strength-speed, strength-resistance, strength-skill, strength-mobility are important.